2017
DOI: 10.1590/s0104-12902017162160
|View full text |Cite
|
Sign up to set email alerts
|

Percepção da saúde bucal em mulheres com perdas dentárias extensas

Abstract: Percepção da saúde bucal em mulheres com perdas dentárias extensas Perception of oral health in women with extensive dental losses ResumoEste escrito tem por objetivo analisar a percepção de mulheres com perdas dentárias extensas sob o olhar da bucalidade. A pesquisa foi realizada com mulheres com essas características em uma cidade de pequeno porte no estado de Santa Catarina. A entrevista semiestruturada produziu narrativas que foram gravadas e transcritas. Depois da coleta dos dados, realizou-se a análise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 15 publications
0
9
0
20
Order By: Relevance
“…Regarding eating difficulties, users of poorly adapted prostheses reported having to interrupt meals in situations that can be related to discomfort resulting from prostheses that are unstable during chewing. Users of old and inadequate prostheses suffer since they need to change their food to more creamy/soft ingredients with less nutritional value, since pain and discomfort do not allow consistent chewing of food, therefore directly influencing the quality of life and life expectancy [41].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding eating difficulties, users of poorly adapted prostheses reported having to interrupt meals in situations that can be related to discomfort resulting from prostheses that are unstable during chewing. Users of old and inadequate prostheses suffer since they need to change their food to more creamy/soft ingredients with less nutritional value, since pain and discomfort do not allow consistent chewing of food, therefore directly influencing the quality of life and life expectancy [41].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown an important impact on oral conditions due to the fact of being female [ 28 30 ]. Other studies have found a disadvantage for women concerning chewing, communication, and pain difficulties [ 31 ], negative self-assessment of oral health [ 32 ], and tooth loss [ 3 ]. However, there is no consensus in the literature, and there is one study reporting the absence of gender differences [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neste contexto, esses problemas bucais da população geriátrica, podem ser explicados pela perpetuação da equivocada concepção do modelo odontológico curativo-resolutivo e a associação negativa do cirurgião-dentista (CD) como técnico e mutilador 6,8,9 . Além disso, o baixo uso dos serviços odontológicos, recorrendo ao tratamento somente na presença de dor e percepção reabilitadora, destacam tais pensamentos 6,8,10 .…”
Section: Introductionunclassified